Inteligencia de mercados para la exportación de mermelada orgánica de durazno con aloe vera de la empresa “Duraloe” del cantón Pimampiro provincia de Imbabura - Reinoso Benavides, Erick Steven (2024)
DURALOE company is located in the province of Imbabura, in the canton Pimampiro, is a new company which works with the association of producers of peach and aloe vera in the town, is dedicated to the production of pulp and peach jam 100% natural and pure, for marketing at local, provincial and national level. The objective of this research is to conduct a market intelligence for the export of peach jam and aloe vera of DURALOE company, knowing that the company currently wants to internationalize its product. The purpose of this research was to study the importance of market intelligence by knowing a target market to which the company is going to export. As a means of search, we worked with information from official websites such as TradeMap, Pro Ecuador, MIPRO, among others. In addition, research instruments are used to collect data in order to take the necessary steps to carry out the export plan and the implementation of the project. The peach and aloe vera jam covers the local demand and now with this research it is determined that the target market is Germany, being the country that has the greatest acceptance\; it is also worth mentioning that the internationalization of several Ecuadorian companies and brands that expanded to international markets have shown that there are opportunities to grow in specific niches.